Plan de importación de triplex para la ferretira san antonio desde el mercado chileno - Tito Cisneros, Francisco Aron (2024)
The business plan for the importation of the triplex board from Chile for San Antonio Hardware, was born as a need for internationalization of the company with the aim of becoming direct importers of this Chilean product, through research and field data collection, to determine the profitability of the project, starting with the segmentation of the family population of San Antonio, which gave a total of 44 surveys and the realization of 2 interviews one to the manager of the hardware store and the other to the president of the association of artisans of San Antonio giving very positive results for the development of the market study which helped the development of the project with the technical, organizational, financial study and financial evaluation that helped to determine the feasibility of the import plan to be carried out. It is concluded that the thesis presented addresses a strategic procedure for the fulfillment of a project that demonstrates that it is feasible for 'Ferretería San Antonio' to import Triplex from the Chilean market.